Območja izboljšanega poslovanja in njihov vpliv na teritorialne blagovne znamke - Almeida, Giovana Goretti Feijó (Urbani izziv, 2024)
Numerous cities worldwide employ business improvement districts (BIDs) to manage their central areas. This article analyses the contribution of BIDs to cities’ territorial brands. Employing a case study methodology, we utilize the “territorial brand in regional development” (TBRD) matrix for qualitative analysis of selected BIDs. The findings underscore BIDs’ role as a versatile territorial brand in regional development shaping strategic discussions and fostering local, regional, and global reputations. It can be concluded that BIDs significantly enhance the territorial brand of their cities, receiving endorsement across various scales. Furthermore, urban and regional development processes involve political and cultural discussions, and this article revealed that BIDs are an active player in these discussions.